2019
DOI: 10.1111/bjd.18237
|View full text |Cite
|
Sign up to set email alerts
|

A new ex vivo human oral mucosa model reveals that p38 MAPK inhibition is not effective in preventing autoantibody‐induced mucosal blistering in pemphigus

Abstract: Summary Background Pemphigus vulgaris (PV) is an autoimmune disease characterized by blister formation in the epidermis and oral mucosa due to loss of keratinocyte cohesion. Autoantibodies present in patients with PV (PV‐IgG) are known to primarily target desmoglein (Dsg)1 and Dsg3 in desmosomes. The mucosal‐dominant subtype of PV (mdPV) is caused by PV‐IgG autoantibodies against the cadherin‐type adhesion molecule Dsg3. p38 mitogen‐activated protein kinase (p38MAPK) signalling has been characterized as an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 33 publications
0
39
0
1
Order By: Relevance
“…Using a similar model, blister formation in human skin has been sufficiently blocked by inhibition of p38MAPK signaling (18) whereas in mucosa explant culture inhibition of p38MAPK was not protective against PV-IgG-induced blistering (19). Previous experiments have demonstrated that inhibition of PKC and ERK pathways sufficiently abrogated cell dissociation in keratinocyte cell cultures (17, 20, 25) and deactivation of PKC signaling in neonatal pemphigus mouse model effectively blunted blister formation (30, 31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a similar model, blister formation in human skin has been sufficiently blocked by inhibition of p38MAPK signaling (18) whereas in mucosa explant culture inhibition of p38MAPK was not protective against PV-IgG-induced blistering (19). Previous experiments have demonstrated that inhibition of PKC and ERK pathways sufficiently abrogated cell dissociation in keratinocyte cell cultures (17, 20, 25) and deactivation of PKC signaling in neonatal pemphigus mouse model effectively blunted blister formation (30, 31).…”
Section: Discussionmentioning
confidence: 99%
“…It is activated secondary to PV-IgG binding and its phosphorylation is detected in lesioned skin of PV patients (14) and in keratinocyte cell cultures treated with PV-IgG (15, 16). Interestingly, pharmacologic inhibition of p38MAPK effectively prevented all PV-IgG-induced features of the disease in keratinocyte cell cultures (15, 17), animal models (8), and in ex vivo human skin (18) but not in an ex vivo model of human mucosa (19). As a result, p38MAPK is believed to be central in PV pathogenesis, at least with respect to skin blister formation.…”
Section: Introductionmentioning
confidence: 99%
“…Upon targeting of Dsg1, Ca 2+ influx is induced and the ERK pathway is activated. In contrast, after binding of Dsg3-specific IgG, signaling via p38MAPK occurs in the epidermis but not in mucosal tissues, and SRC family of protein tyrosine kinases and EGFR pathways are activated ( 51 , 52 ). Current data also strongly suggest that, in addition to Dsg1/3 autoantibodies, non-Dsg antibodies, as well as soluble Fas ligand contribute to the pemphigus phenotype ( 53 56 ).…”
Section: Functionally Relevant Molecules and Pathways In Pemphigus Anmentioning
confidence: 99%
“…While in oncology personalized medicine approaches are becoming relatively well established, personalized treatment decisions have just begun to emerge in chronic inflammatory diseases. One such example is the article by Egu and colleagues in this issue of the BJD . Herein the authors first established a new model of mucosal pemphigus vulgaris (PV) and then contrasted the molecular pathways leading to blistering in this disease in skin and mucosa.…”
mentioning
confidence: 99%
“…However, despite the fact that both the skin and mucosa are affected by pemphigus, most research in pemphigus is carried out using keratinocytes – hence, these insights are limited to the skin lesions of pemphigus. In this issue, Egu and colleagues, following their work on p38 MAPK in the skin, investigated the role of p38 MAPK in mucosal pemphigus . For this purpose, they established a human ex vivo mucosal cell culture system to evaluate the p38 MAPK dependency of mucosal blister formation.…”
mentioning
confidence: 99%